Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
`        Please solve the below problem:If y=x^1/3-x^-1/3, then y^3+3y=?`
one year ago

54 Points
```							We are given that:y=x1/3 – x-1/3 The expression asked to solve can be rearranged into:y2 (y + 3) So, first we will evaluate the value of y2:Therefore, by squaring on both the sides we get: y2 = (x1/3 – x-1/3)2    = x2/3 + x-2/3 – 2 Now, by inserting the value we get:= y (x2/3 + x-2/3 – 2 + 3)= (x1/3 – x-1/3 )(x2/3 + x-2/3 + 1)= x + x-1/3 + x1/3 –  x1/3 – 1/x –  x-1/3 By, cancelling terms we get our final expression:= x – 1/x
```
one year ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »

### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution

### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions